2015
DOI: 10.1016/j.jped.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two maintenance electrolyte solutions in children in the postoperative appendectomy period: a randomized, controlled trial

Abstract: In the post-appendectomy period, the use of hypotonic solution (30 mEq/L, 0.18%) did not increase the risk of hyponatremia when compared to isotonic saline. The use of isotonic solution (150 mEq/L, 0.9%) did not favor hypernatremia in these patients. Children who received hypotonic solution showed higher cumulative fluid balance in the preoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Yet, water retention due to excess amounts of sodium might be associated with increased weight in a few patients. In the largest of 3 earlier studies reporting weight gain, with 110 acutely ill children, greater weight gain among children receiving isotonic fluid therapy was observed, but the difference was not statistically significant . The greater weight gain suggested by the present study may be clinically insignificant for most pediatric patients, but it might cause a risk for vulnerable patient populations …”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Yet, water retention due to excess amounts of sodium might be associated with increased weight in a few patients. In the largest of 3 earlier studies reporting weight gain, with 110 acutely ill children, greater weight gain among children receiving isotonic fluid therapy was observed, but the difference was not statistically significant . The greater weight gain suggested by the present study may be clinically insignificant for most pediatric patients, but it might cause a risk for vulnerable patient populations …”
Section: Discussioncontrasting
confidence: 70%
“…In the largest 17 of 3 earlier studies reporting weight gain, with 110 acutely ill children, greater weight gain among children receiving isotonic fluid therapy was observed, but the difference was not statistically significant. 17,28,29 The greater weight gain suggested by the present study may be clinically insignificant for most pediatric patients, but it might cause a risk for vulnerable patient populations. 30 The risk of hyponatremia was not increased in patients receiving moderately hypotonic fluid therapy, which is contrary to the risk reported earlier.…”
Section: Discussionmentioning
confidence: 78%
“…There are 6 randomized clinical trials 31,49,50,53,56,59 in which researchers enrolled only ICU patients, and all but one 50 revealed a significant difference favoring isotonic IVFs for the prevention of hyponatremia. Researchers in 8 randomized clinical trials enrolled exclusively patients in a general ward setting, 32,51,52,54,55,57,58,60 and those in all but 2 32, 57 found a significant reduction in hyponatremia among those receiving isotonic IVFs. McNab et al 35 enrolled patients in both the ICU and general surgical ward, and they were at similar risk for developing hyponatremia.…”
Section: Varying Acuity (Icu Versus General Ward)mentioning
confidence: 99%
“…Children 66 In the non-ICU population, researchers in only a handful of studies mention an association between fluid tonicity and volume overload (or "weight gain"). 20,59,60 Choong et al 20 reported on "overhydration" as estimated by using total weight gain, finding no significant difference between isotonic and hypotonic IVF administration. In the metaanalyses that encompass 12 different RCTs and more than 750 children, neither weight nor net fluid balance is discussed.…”
Section: Fluid Overloadmentioning
confidence: 99%